The Biological Role of Klotho Protein in the Development of Cardiovascular Diseases. (24th December 2018) - Olejnik, Agnieszka; Franczak, Aleksandra; Krzywonos-Zawadzka, Anna; Kałużna-Oleksy, Marta; Bil-Lula, Iwona
Abstract : Klotho is a membrane-bound or soluble antiaging protein, whose protective activity is essential for a proper function of many organs. In 1997, an accidental insertion of a transgene led to creation of transgenic mice with several age-related disorders. In Klotho-deficient mice, the inherited phenotypes closely resemble human aging, while in an animal model of Klotho overexpression, the lifespan is extended. Klotho protein is detected mainly in the kidneys and brain. It is a coreceptor for fibroblast growth factor and hence is involved in maintaining endocrine system homeostasis. Furthermore, an inhibition of insulin/insulin-like growth factor-1 signaling pathway by Klotho regulates oxidative stress and reduces cell death. The association between serum Klotho and the classic risk factors, as well as the clinical history of cardiovascular disease, was also shown. There are a lot of evidences that Klotho deficiency correlates with the occurrence and development of coronary artery disease, atherosclerosis, myocardial infarction, and left ventricular hypertrophy. Therefore, an involvement of Klotho in the signaling pathways and in regulation of a proper cell metabolism could be a crucial factor in the cardiac and vascular protection. It is also well established that Klotho protein enhances the antioxidative response via augmented production of superoxide dismutase and reduced generation of reactive oxygen species. Recent studies have proven an expression of Klotho in cardiomyocytes and its increased expression in stress-related heart injury. Thus, the antioxidative and antiapoptotic activity of Klotho could be considered as the novel protective factor in cardiovascular disease and heart injury.